Influence of n = 1 resonant magnetic perturbation on flow and turbulence towards L-H transition - Y. Zhang; M. Jiang; Z.B. Guo; P.H. Diamond; W.X. Guo; J.Q. Xu; N. Zhang; Z. Wang; Z.J. Li; Y. Zhou; A.S. Liang; T.F. Sun; et al. (Nuclear Fusion)
The application of resonant magnetic perturbation (RMP) with toroidal mode number n  = 1 on HL-3 tokamak inhibits the L-H transition at specific heating power. Following RMP application, the electron density increases in the outer plasma region ( ρ  > 0.85, where ρ is the normalized toroidal flux), while the electron/ion temperature decreases. Notably, the equilibrium flow shear in the edge region is substantially reduced. This reduction, combined with enhanced micro-instabilities driven by increased profile gradients, leads to enhanced turbulence levels. Consequently, the diminished flow shear becomes less effective in suppressing turbulence, providing a comprehensive explanation for the inhibited access to H-mode. Through a modified one-dimensional predator–prey model that incorporates the effects of RMP-induced radial magnetic perturbations, we have conducted a quantitative analysis of the turbulence and flow dynamics during the L-H transition process. Our results indicate that as the strength of magnetic perturbation increases, the turbulence intensity increases and edge flow shear decreases, in agreement with experimental observations. Additionally, we found that the L-H transition power threshold increases almost linearly with the square of the radial magnetic perturbation intensity. These results enhance our understanding of RMP-induced changes in edge plasma transport, providing valuable insights for optimizing the operation of future tokamaks and improving the performance of fusion reactors.